2022
DOI: 10.1136/bmj-2022-072065
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine effectiveness of primary series and booster doses against covid-19 associated hospital admissions in the United States: living test negative design study

Abstract: Objective To compare the effectiveness of a primary covid-19 vaccine series plus booster doses with a primary series alone for the prevention of hospital admission with omicron related covid-19 in the United States. Design Multicenter observational case-control study with a test negative design. Setting Hospitals in 18 US states. Participants 4760 adults admitted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 46 publications
(81 reference statements)
2
60
0
Order By: Relevance
“…Although chronic conditions have been observed to reduce effectiveness [ 30 ], sample size was insufficient to differentiate VE by number of conditions. Fourth, the influence of prior infection on VE is not fully known due to a lack of definitive prior infection history among hospitalized patients (eg, inability or refusal to answer) and the likelihood of undercapture [ 31 ]; however, a previous sensitivity analysis showed that effectiveness did not change after removing patients with prior infection [ 13 ]. Fifth, it was not possible to estimate potential waning of VE due to the time-limited nature of the study, but previous analyses have shown waning for booster doses with increasing time since vaccination [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although chronic conditions have been observed to reduce effectiveness [ 30 ], sample size was insufficient to differentiate VE by number of conditions. Fourth, the influence of prior infection on VE is not fully known due to a lack of definitive prior infection history among hospitalized patients (eg, inability or refusal to answer) and the likelihood of undercapture [ 31 ]; however, a previous sensitivity analysis showed that effectiveness did not change after removing patients with prior infection [ 13 ]. Fifth, it was not possible to estimate potential waning of VE due to the time-limited nature of the study, but previous analyses have shown waning for booster doses with increasing time since vaccination [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…During December 25, 2021–April 4, 2022, a period in which the B.1.1.529 (Omicron) variant of SARS-CoV-2 was close to 100% predominant (including an estimated >90% BA.1 or BA.2 lineages) [ 13 ], adults admitted to 21 hospitals in 18 US states within the Influenza or Other Viruses in the Acutely Ill (IVY) Network [ 2 , 4 , 14 , 15 ] who received testing for SARS-CoV-2 were included in a VE analysis. The analysis start date of December 25, 2021 was approximately 1 month after the emergency use authorization of a first booster dose (following a primary series of 2 mRNA doses or 1 Janssen dose) was expanded to include all adults aged ≥18 years [ 16 ] and coincided with the start of the period when the SARS-CoV-2 Omicron variant dominated in the United States.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A bivalent mRNA vaccine ("updated vaccine") booster containing components of the original (ancestral) strain and the BA.4/BA.5 is recommended [80]. This was supported by Adams et al, who observed that an mRNA vaccine booster dose provided additional benefit beyond a primary vaccine series alone for preventing hospital admissions with Omicron related COVID-19 during the first six months of 2022 in the US [81]. In addition, a Phase Ⅱ/Ⅲ clinical trial (NCT04927065) reported that 50 μg bivalent Omicron-containing booster mRNA vaccine (named mRNA-1273.214, Moderna), which combines mRNA-1273.529 and mRNA-1273, elicited higher neutralizing antibody response against BA.4/5 than immune response elicited with mRNA-1273 28 days after immunization, without evident safety concerns.…”
Section: New Vaccines Against Omicronmentioning
confidence: 99%
“…When the Delta variant became predominant (from early to late 2021), overall, VE in preventing breakthrough infections was reduced from 90% to 78–81% [ 16 ]. When we experienced the Omicron wave from late 2021 to early 2022, the BNT162b2 vaccine showed reduced effectiveness in preventing symptomatic SARS-CoV-2 infection compared to during the Delta wave period [ 17 ], with recommendations for a booster vaccination to be given to prevent Omicron-related hospitalization/illness [ 18 , 19 ]. With the advent of newer variants (e.g., BA.4, BA.5, XBB) with enhanced immune evasion [ 20 , 21 ], VE against hospitalization was further compromised [ 22 ], with calls for additional doses of bivalent vaccine to improve protection [ 23 , 24 ].…”
Section: Environmental Factors That Can Impact Vementioning
confidence: 99%